BIBLIOMETERIC ANALYSIS OF POLICY INTERVENTION ARTICLES CONDUCTED BY INTERNATIONAL DONOR AGENCIES IN THE SCOPUS DATABASE - Iriansyah, Nova; Suganti, Yogi Suprayogi; Sumadinata, Widya Setiabudi; Widianingsih, Ida (Erudio Journal of Educational Innovation, 2024)
This study aims to conduct a bibliometric analysis of articles on policy interventions undertaken by international donor agencies in the Scopus database. This study uses a bibliometric analysis based on the Scopus database. One hundred one articles on policy interventions from international donor agencies in the Scopus database. Then classified by year of publication, author, affiliation, keywords and journal-title. The author also conducts a literature review of articles regarding policy interventions carried out by international donor agencies in the Scopus database. Analysis of bibliographical characteristics and content of articles regarding policy interventions carried out by international donor agencies in the Scopus database has been partially answered. Analysis of bibliographical characteristics, such as number of citations and keywords, provides valuable insights into trends and focus of the literature. This research provides valuable insight into the characteristics and content of articles on policy interventions by international donors. However, further research is needed to thoroughly understand each article's content and findings and develop new knowledge in this field. population.